Alginate-based hydrogel platform embedding silver nanoparticles and cisplatin: characterization of the synergistic effect on a breast cancer cell line - Maher, Shaimaa; Kalil, Haitham; Liu, Guiming; Sossey-Alaoui, Khalid; Bayachou, Mekki (Frontiers in Molecular Biosciences, 2023)
Breast cancer is a significant cause of mortality in women globally, and current treatment approaches face challenges due to side effects and drug resistance. Nanotechnology offers promising solutions by enabling targeted drug delivery and minimizing toxicity to normal tissues. In this study, we developed a composite platform called (Alg-AgNPs-CisPt), consisting of silver nanoparticles coated with an alginate hydrogel embedding cisplatin. We examined the effectiveness of this nanocomplex in induce synergistic cytotoxic effects on breast cancer cells. Characterization using various analytical techniques confirmed the composition of the nanocomplex and the distribution of its components.Cytotoxicity assays and apoptosis analysis demonstrated that the nanocomplex exhibited greater efficacy against breast cancer cells compared to AgNPs or cisplatin as standalone treatments.Moreover, the nanocomplex was found to enhance intracellular reactive oxygen species levels, further validating its efficacy. The synergistic action of the nanocomplex constituents offers potential advantages in reducing side effects associated with higher doses of cisplatin as a standalone treatment.Overall, this study highlights the potential of the (Alg-AgNPs-CisPt) nanocomplex as a promising platform embedding components with synergistic action against breast cancer cells.